2007
DOI: 10.1002/ijc.22532
|View full text |Cite
|
Sign up to set email alerts
|

Less aggressive treatment and worse overall survival in cancer patients with diabetes: A large population based analysis

Abstract: The purpose of this study was to document the prevalence of diabetes among newly diagnosed cancer patients and to evaluate the influence of diabetes on stage at diagnosis, treatment and overall survival. We performed a population‐based analyses of all 58,498 cancer patients newly diagnosed between 1995 and 2002 in the registration area of the Eindhoven Cancer Registry. Stage of cancer, cancer treatment and comorbidities were actively collected by hospital medical records review. Follow‐up of all patients was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
306
5
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 284 publications
(325 citation statements)
references
References 37 publications
13
306
5
1
Order By: Relevance
“…Another study showed that individuals with diabetes and recent HbA 1c values >9.0% (75 mmol/mol; OR 1.5; 95% CI 1.3, 1.7) had higher mortality than those with recent 'normal' HbA 1c values between 6.5% (48 mmol/mol) and 9% (75 mmol/mol) [18]. Thus, the drop in MPR observed among patients with cancer in our study might have negatively influenced survival via the aforementioned mechanisms and may (partly) explain the established association between diabetes, cancer and survival [1][2][3].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Another study showed that individuals with diabetes and recent HbA 1c values >9.0% (75 mmol/mol; OR 1.5; 95% CI 1.3, 1.7) had higher mortality than those with recent 'normal' HbA 1c values between 6.5% (48 mmol/mol) and 9% (75 mmol/mol) [18]. Thus, the drop in MPR observed among patients with cancer in our study might have negatively influenced survival via the aforementioned mechanisms and may (partly) explain the established association between diabetes, cancer and survival [1][2][3].…”
Section: Discussionmentioning
confidence: 57%
“…Although the impact of cancer was more pronounced among cancers with a worse prognosis and among those with more advanced TNM stages, the difference in prognosis associated with these cancers seemed to only partly explain the impact of cancer on medication adherence. The decline in adherence seen among users of GLDs with cancer might negatively affect survival and (partly) explain the established association between diabetes, cancer and survival [1][2][3]. In future studies, the reason for the decline in MPR needs to be further elucidated among the different cancer types-is it the patient who prioritises the fight against cancer or the advice of the physician to stop the treatment?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is limited and conflicting. Although the few prior studies (Park et al, 2006;Van de Poll et al, 2007;Win et al, 2008;Varlotto et al, 2011) showed that pre-existing DM that at the time of diagnosis strongly associated increase OS. Contrary to this, the meta-analysis analysis by Barone et al (2008) and the study of Tammemagi et al (2003) no observed this relationship between diabetes and lung cancer.…”
Section: Discussionmentioning
confidence: 95%
“…It was demonstrated previously parameters that good PS, disease stage, age and weight loss associated as strong prognostic factors whereas DM was not clearly or consistently identified (Park et al, 2006;Van de Poll et al, 2007;Barone et al, 2008;Win et al, 2008;Varlotto et al, 2011).…”
Section: Introductionmentioning
confidence: 95%